2014
DOI: 10.1111/exd.12546
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptional profiling of human Merkel cells and Merkel cell carcinoma

Abstract: Additional supporting data may be found in the supplementary information of this article.Data S1. Materials and methods Figure S1. Statistical analysis of PCNA-positive cell ratio in control and Wnt5a TG epidermis at P21 and P71. Figure S2. Skin biopsy staining at the morphogenesis stage and P28. Figure S3. Wnt5a is over-expressed in the epidermis under the control of human K14 promoter. Abstract: Merkel cell carcinoma is believed to be derived from Merkel cells after infection by Merkel cell polyomavirus (MCP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…However, it is important to mention that the origin of MCC is controversial, and it is yet unclear whether MCC originates from Merkel cells. [214][215][216][217][218][219] Supporting this notion, recent studies have identified a role for LSD1 in human MCC cell proliferation and survival. LSD1 is a lysine-specific histone demethylase that removes mono-and di-methylation from histone H3K4, which are associated with active transcription.…”
Section: Oss-ronen and Cohenmentioning
confidence: 85%
“…However, it is important to mention that the origin of MCC is controversial, and it is yet unclear whether MCC originates from Merkel cells. [214][215][216][217][218][219] Supporting this notion, recent studies have identified a role for LSD1 in human MCC cell proliferation and survival. LSD1 is a lysine-specific histone demethylase that removes mono-and di-methylation from histone H3K4, which are associated with active transcription.…”
Section: Oss-ronen and Cohenmentioning
confidence: 85%
“…One of the few distinguishing factors between MCPyV-negative and MCPyV-positive MCC was the increased expression of cell adhesion molecules seen in MCPyV-negative MCC. 124 No definitive conclusions could be drawn; however, the study identifies a number of genes and pathways that can be further evaluated in the search for novel treatment strategies. Both antiviral and immune-modulating therapeutic options are being explored.…”
Section: Potential Therapiesmentioning
confidence: 99%
“…The recent discovery of MCPyV and the knowledge of molecular pathways involved in the development of MCC has led to significant research into new therapeutic options. 98 DNA mutations in MCC-related genes have recently been discovered (PDE4DIP, MLL3, ERCC5, AURKB, ATR, TSHR, and BCL2L2), however, further investigation for potential therapeutic targets is required. 42 Both antiviral and immune modulating therapeutic options are being explored and the potential for MCPyV vaccination is currently being examined in the mouse model.…”
Section: Potential Future Therapiesmentioning
confidence: 99%
“…Although the current NCCN guidelines do not comment on potential future therapies for obvious reasons, a brief review of the therapeutic horizon for MCC is warranted. The recent discovery of MCPyV and the knowledge of molecular pathways involved in the development of MCC has led to significant research into new therapeutic options . DNA mutations in MCC‐related genes have recently been discovered (PDE4DIP, MLL3, ERCC5, AURKB, ATR, TSHR, and BCL2L2), however, further investigation for potential therapeutic targets is required .…”
Section: Introductionmentioning
confidence: 99%